The Performance of Discus (Symphysodon discus) Hatchery in Joel Nararya Farm, Sukarame, Bandar Lampung - Muhammad Browijoyo Santanumurti (Universitas Islam Lamongan, 2021)
Indonesia has biodiversity in ornamental fish commodities. ). One of the ornamental fish that has the potential to be developed is the discus fish. The hatchery of discus fish is an important activity in the aquaculture process. This study aimed to determine the performance of discus fish hatchery in Joel Nararya Farm, Sukarame, Bandar Lampung. This study observed 2 broodstock of hatchery prouction, code A (Female Pigeon x Male Pigeon) and B (Female Pigeon x Male Blue Turqoise). This study showed that the fecundity was 153 eggs for A and 160 eggs for B. The fertilization rate showed a value of 73% for codes A and B. The hatching rate value indicated a value of 15% for code A and 64% for code B. The performance of discus fish hatchery was not optimum. The farm should use 2:2 ratio male and female to increase the eggs production. The code A hatchery aquarium was also too close to the passing places of broodstock so that they were easily stressed and affected the hatching rate. It need to be replaced to proper location.